PENGARUH KUALITAS JASA, CITRA PERUSAHAAN, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PRODUK JASA UMROH PT. SILVER SILK TOUR & TRAVEL PEKANBARU - Nurma Yulis; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted at PT. Pekanbaru Silver Silk Tour & Travel located on Arifin Ahmad Pekanbaru . The problem in this study is the failure to achieve the target of Umrah congregation over the past five years, this is suspected to be a problem in consumer purchasing decisions. The purpose of this study was to determine the effect of service quality, corporate image, and word of mouth on consumer purchasing decisions of umrah service products of PT. Pekanbaru Silver Silk Tour & Travel. In this study the method used was quantitative descriptive with the SPSS program. The sample of this study was 100 people from the population which amounted to 4,217 obtained from the calculation of the Slovin formula. Data obtained from the results of the questionnaire were then processed to then be tested through SPSS 23. Testing of multiple linear regression analysis from this study was Y = 0.705 + 0.118X1 + 0.423X2+0.247X3. The research that has been done shows the results that respondents' responses to service quality, corporate image and word of mouth in the category of good or agree while in consumer purchasing decisions are in the category of good enough or quite agree. while the t test that has been done shows that the variable quality of service, corporate image and word of mouth partially have a significant effect on consumer purchasing decisions. The results of the F test show that simultaneously service quality, corporate image and word of mouth have a significant effect on consumer purchasing decisions. While the calculation of the coefficient of determination (R2) obtained the value of Adjusted R Square of 0.546. This shows that service quality, corporate image and word of mouth have an influence of 54.6% on consumer purchasing decisions of umrah service products of PT. Pekanbaru Silver Silk Tour & Travel, while the remaining 45.4% is influenced by other variables not included in this study.Keywords: Service Quality, Corporate Image, Word of Mouth, and Consumer Purchasing Decisions